ФОРМУВАННЯ ГОТОВНОСТІ СТУДЕНТІВ ДО САМОМЕНЕДЖМЕНТУ ЯК АКТУАЛЬНА ПЕДАГОГІЧНА ПРОБЛЕМА (Педагогіка вищої та середньої школи, 2022)
This article deals with one of the most important problems in the sphere of éducation now - the problem of formation of readiness of students to the self management.